2019
DOI: 10.3390/ijms20112720
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models for Human Polycystic Ovary Syndrome (PCOS) Focused on the Use of Indirect Hormonal Perturbations: A Review of the Literature

Abstract: Hormonal disturbances, such as hyperandrogenism, are considered important for developing polycystic ovary syndrome (PCOS) in humans. Accordingly, directly hormone-regulated animal models are widely used for studying PCOS, as they replicate several key PCOS features. However, the pathogenesis and treatment of PCOS are still unclear. In this review, we aimed to investigate animal PCOS models and PCOS-like phenotypes in animal experiments without direct hormonal interventions and determine the underlying mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 176 publications
(178 reference statements)
3
36
0
1
Order By: Relevance
“…c. In theca-interstitial cells, Pten deletion produced features of PCOS including hyperandrogenism and early fertility loss (154). Animal models suggest that the PI3K/AKT pathway plays a significant role in the molecular pathology of PCOS (155); the outcome of Pten deletion in theca cells is consistent with this. The involvement of PI3K pathway in PCOS is further demonstrated by the fact that PTEN expression is altered in endometrium of PCOS patients (156).…”
Section: Pten and Pcosmentioning
confidence: 81%
“…c. In theca-interstitial cells, Pten deletion produced features of PCOS including hyperandrogenism and early fertility loss (154). Animal models suggest that the PI3K/AKT pathway plays a significant role in the molecular pathology of PCOS (155); the outcome of Pten deletion in theca cells is consistent with this. The involvement of PI3K pathway in PCOS is further demonstrated by the fact that PTEN expression is altered in endometrium of PCOS patients (156).…”
Section: Pten and Pcosmentioning
confidence: 81%
“…Using the method of insulin resistance combined with hormonal disorders [ 29 ], we firstly replicated a PCOS mouse model [ 30 ], where we then showed that the health care effect of catechins extract on PCOS was related to the anti-inflammatory and anti-matrix degradation effects in the mouse uterus. Importantly, we demonstrated that the continuing healthcare benefit of catechins extract was to rescue hormonal disorders, insulin resistance, and ovarian and uterine pathological changes of PCOS mice by inhibiting STAT3 signaling in the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Some genetically engineered or inherited animal models have shown symptoms of PCOS, which are due to inappropriate hormone exposure or ER changes affecting endocrine homeostasis, leading to the development of ovarian abnormalities and a reduction in fertility [ 46 , 47 ]. Paying attention to animal PCOS models is helpful in order for us to better understand the disease characteristics of PCOS (as shown in Table 1 ).…”
Section: Physiological and Pathological Function Of Ersmentioning
confidence: 99%